Prenatal findings in 1p36 deletion syndrome: New cases and a literature review. (5th July 2019) - Guterman, Sarah; Beneteau, Claire; Redon, Sylvia; Dupont, Céline; Missirian, Chantal; Jaeger, Pauline; Herve, Berenice; Jacquin, Clémence; Douet‐Guilbert, Nathalie; Till, Marianne; Tabet, Anne‐Claude; Moradkhani, Kamran; et al.
Abstract: Objective/Method: 1p36 deletion syndrome is considered to be the most common deletion after 22q11.2 deletion. It is characterized by specific facial features, developmental delay, and organ defects. The primary objective of the present multicenter study was to survey all the cases of 1p36 deletion diagnosed prenatally by French cytogenetics laboratories using a chromosomal microarray. We then compared these new cases with the literature data. Results: Ten new cases were reported. On average, the 1p36 deletion was diagnosed at 19 weeks of gestation. The size of the deletion ranged from 1.6 to 16 Mb. The 1p36 deletion was the only chromosomal abnormality in eight cases and was associated with a complex chromosome 1 rearrangement in the two remaining cases. The invasive diagnostic procedure had always been prompted by abnormal ultrasound findings: elevated nuchal translucency, structural brain abnormality, retrognathia, or a cardiac defect. Multiple anomalies were present in all cases. Discussion: We conclude that 1p36 deletion is not associated with any specific prenatal signs. We suggest that a prenatal observation of ventriculomegaly, congenital heart defect, or facial dysmorphism should prompt the clinician to consider a diagnosis of 1p36 deletion syndrome.